Hormonal doping and androgenization of athletes: a secret program of the German Democratic Republic government - Franke, W.; Berendonk, B. (Clinical Chemistry, 1997)
Several classified documents saved after the collapse of the German Democratic Republic (GDR) in 1990 describe the promotion by the government of the use of drugs, notably androgenic steroids, in high-performance sports (doping). Top-secret doctoral theses, scientific reports, progress reports of grants, proceedings from symposia of experts, and reports of physicians and scientists who served as unofficial collaborators for the Ministry for State Security ("Stasi") reveal that from 1966 on, hundreds of physicians and scientists, including top-ranking professors, performed doping research and administered prescription drugs as well as unapproved experimental drug preparations. Several thousand athletes were treated with androgens every year, including minors of each sex. Special emphasis was placed on administering androgens to women and adolescent girls because this practice proved to be particularly effective for sports performance. Damaging side effects were recorded, some of which required surgical or medical intervention. In addition, several prominent scientists and sports physicians of the GDR contributed to the development of methods of drug administration that would evade detection by international doping controls.